SARS LIABLE FOR CHEQUES LOST OR STOLEN IN THE POST Stabilpave v SARS (615/12) [2013] ZASCA 128 - Darren Subramanien (Obiter, 2014)
The Supreme Court of Appeal (SCA) in Stabilpave v SARS (615/12) [2013] ZASCA 128 was asked to decide on the assumption of risk where a cheque issued by the South African Revenue Services was intercepted through the post and subsequently misappropriated by thieves. The judgment of the court is significant as it stated clearly that any agreement “about the particular mode of performance” or “as to the manner of payment” will only be reached if the creditor stipulates (or requests orauthorizes) a particular mode of payment and the debtor accedes to the request. According to the court, due to the fact that the appellant had not requested the refund by cheque, SARS carried the risk of theft or loss of the cheque.